Detection of unusually high transcriptomic and proteomic abundance of bromoform-synthesizing halogenase in marine macroalgae Asparagopsis taxiformis - Lin, Zhenjian; Islam, Shahima; Hargrave, Matthew S.; Singh, Rakesh; Zhou, Lingjie; Xie, Ramon; Smith, Jennifer E.; Schmidt, Eric W.; Agarwal, Vinayak (Frontiers in Marine Science, 2025)
Halogenated molecules produced by marine algae are thought to be defensive secondary metabolites. The extraordinarily high concentration of bromoform in the seaweed Asparagopsis—up to 8% dry tissue weight—challenges the exclusivity of this paradigm. In this report, we provide evidence that the mbb1 gene which encodes the bromoform producing halogenase is among the most highly transcribed genes in Asparagopsis tissue, with the resulting Mbb1 protein abundance rivaling that of enzymes involved in photosynthesis and carbon fixation. When the seaweed was stressed with light, transcripts for both mbb1 and for proteins involved in photosynthesis were significantly downregulated. Conversely, heat stress modestly upregulated some photosynthesis genes but had no impact on mbb1. Taken together, these findings allow us to posit that bromoform production is not solely a stress-response or self-defense mechanism for A. taxiformis. Instead, we propose that the halogenase Mbb1 likely fulfils a primary metabolic function in this red alga thusly reconceptualizing halogenation biochemistry and pulling it out of the domain of natural product biosynthesis alone.